Konteks Late Antiquity dan Analisis Struktur Mikro sebagai Counter atas Skeptisisme Orisinalitas Teks Al-Qur’an: - Adrika Fitrotul Aini; Asep Nahrul Musadad (SUHUF, 2017)
This article tries to discuss the reading of Angelika Neuwirth to the holy Qur'an by using critical historical approach through the focus of Qur'anic study before canonical phase. The reading by involving "late antiquity" document is considered to be a comprehensive approach to look at the originality of the text of the Qur'an historically. The Western scholars before Neuwirth were very sceptical to the study of the Qur'an. The method of Angelika Neuwirth to see the position of the Qur'an with other previous texts--"late antique"--and to place it in the historical complexity as a communication process is worth taking into account. This study examines the relationship of the Qur'an to the late antiquity tradition and Neuwirth's offer to the approach model of intertextuality and the microstructure of the Qur'an. The approaches being used in this study are historic-philosophical approach and and descriptive-interpretative one. Eventually, Neuwirth comes to conclusion that the text of the Qur'an has a strong historical roots in its position as a post-Biblical texts. Neuwirth shows the accommodation to the significance and importance of the context of late antiquity to see the Qur'an as a post-Biblical literature. Neuwirth idea has a great contribution to to the development of the study of the Qur'an in the West in dialogical-academical athmosphere.